Liquid crystal alignment agent of nitrogen-containing heterocyclic polysiloxane and application thereof
By introducing polysiloxane with nitrogen-containing heterocyclic rings into the liquid crystal alignment agent, the problem of insufficient friction resistance during friction treatment of liquid crystal display elements is solved, high friction resistance and good liquid crystal orientation are achieved, highlights are reduced and high voltage retention rate is maintained.
Patent Information
- Application Number
- CN202410978116.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-07-19
AI Technical Summary
During the frictional treatment of the existing liquid crystal display elements, the friction resistance of the liquid crystal alignment film is insufficient, resulting in light leakage from the peripheral part of the spacer, resulting in bright spot problems.
Polysiloxane containing nitrogen heterocycle is used as a component of the liquid crystal alignment agent to form a liquid crystal alignment film with high friction resistance and good liquid crystal alignment by synthesizing polymer A, polymer B and organic solvents.
The friction resistance of the liquid crystal display element is significantly improved, and the highlights caused by friction are reduced, ensuring good liquid crystal orientation and high voltage retention rate.
Smart Images

Figure CN118931557B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a liquid crystal alignment agent and application thereof, in particular to a liquid crystal alignment agent of nitrogen-containing heterocyclic polysiloxane and application thereof, belonging to the technical field of functional polymer materials. Background Art
[0002] Liquid crystal display components are widely used in mobile phones, computer monitors, televisions, car displays, etc. In recent years, with the increasing demand for display components such as car navigation and instruments used outdoors or in high temperature and high humidity environments, as well as large-size liquid crystal displays, higher requirements have been placed on the performance of liquid crystal display components such as afterimage and high temperature resistance.
[0003] The liquid crystal display element includes a liquid crystal orientation film that controls the orientation direction of the liquid crystal molecules, a liquid crystal layer that controls the brightness of the transmitted light by rotating the liquid crystal molecules, a color filter (RGB) that can produce light of different colors, pixel electrodes and common electrodes that apply an electric field to the liquid crystal layer, a thin film transistor (TFT) that controls the on and off of the electrical signal supplied to the pixel electrode, and a glass substrate carrier.
[0004] The liquid crystal alignment film is closely related to the display quality of the liquid crystal display element. In addition to ensuring that the liquid crystal molecules have a good orientation, the transmittance, afterimage and friction resistance must also be improved.
[0005] Generally, there are two ways to treat the alignment of liquid crystal alignment films. One is friction alignment, which uses flannel or the like to rub the liquid crystal alignment film in a certain direction to produce grooves on the surface of the liquid crystal alignment film, so that the liquid crystal molecules are arranged in the direction of the grooves; the other is photo-alignment, which uses linear UV polarized light with a wavelength of 254nm, 313nm or 365nm to irradiate the liquid crystal alignment film in a certain direction, so that the molecular chains parallel to the direction of the polarized light are broken, and the liquid crystal molecules are arranged in a direction perpendicular to the polarized light. As a frictionless alignment treatment method, the photo-alignment method has the advantage of being produced in industry using a simple manufacturing process, and is widely used. In particular, in in-plane switching (IPS) type and fringe field switching (FFS) type liquid crystal elements, by using the liquid crystal alignment film obtained by the photo-alignment method, it is expected that the contrast and viewing angle characteristics of the liquid crystal display element will be improved.
[0006] However, with the popularity of touch-sensitive liquid crystal display elements, users frequently press the liquid crystal display elements with their fingers. At this time, the spacers inside the liquid crystal display element move inside the liquid crystal display element and rub the liquid crystal alignment film. The liquid crystal alignment film rubbed by the spacers cannot restrict the orientation of the liquid crystal, and light leaks from the periphery of the spacers and appears as bright spots.
[0007] In the prior art, various additives are usually added to the liquid crystal alignment agent used to make the liquid crystal alignment film to improve the friction resistance of the liquid crystal alignment film. In patent CN104115057A, a compound with a blocked isocyanate group is added to improve the friction resistance of the liquid crystal alignment film. In patent CN111095091A, a liquid crystal alignment agent containing a polymer with an oxazoline skeleton is proposed, which is not easy to cause film peeling, damage, etc. during friction treatment. Summary of the invention
[0008] The object of the present invention is to provide a liquid crystal alignment agent, in which nitrogen-containing heterocyclic polysiloxane is introduced, the friction resistance of a liquid crystal alignment film formed by the liquid crystal alignment agent is improved, and the liquid crystal alignment agent has good liquid crystal orientation and high voltage holding rate.
[0009] The liquid crystal aligning agent of this invention contains the following (A) component, (B) component, and (C) component.
[0010] Component (A): polymer A, at least one selected from nitrogen-containing heterocyclic polysiloxanes represented by the following formula (1).
[0011] (B) Component: polymer B, at least one selected from the group consisting of polyamic acid, polyimide, polyamic acid ester, polyorganosiloxane and poly(meth)acrylate.
[0012] (C) ingredient: organic solvent.
[0013] Furthermore, the nitrogen-containing heterocyclic polysiloxane has the structural formula (1):
[0014]
[0015] In formula (1), Y is a nitrogen-containing heterocyclic organic group. Specifically, Y can be selected from one, two or more structures shown in the following formulas (2) to (5), and * represents an insertion site:
[0016]
[0017] Furthermore, in the above formulae (2) to (5), R1 is selected from a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an alkoxy group having 1 to 20 carbon atoms. Specifically, the alkyl group or alkoxy group having 1 to 20 carbon atoms may be an alkyl group such as methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, etc., and may be an alkoxy group such as hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxypropyl acrylate, etc. Preferably, R1 is selected from a hydrogen atom, methyl, ethyl, butyl, hydroxyethyl methacrylate.
[0018] Furthermore, in the above formulae (2) to (5), the W group is selected from a nitrogen-containing heterocyclic structure, such as a structure containing a triazole group, a tetrazolyl group, a triazine group, an imidazole group, an oxazolyl group, etc.;
[0019] Preferably, W is at least one of the structures ①, ②, and ③ in the following formula (6), and * represents an insertion site:
[0020]
[0021] In formula (6), R2, R3, R4, R5, and R6 are independently selected from at least one of a hydrogen atom and a hydrocarbon group having 1 to 10 carbon atoms. The hydrocarbon group having 1 to 10 carbon atoms may be an alkyl group such as methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, pentyl, hexyl, heptyl, octyl, nonyl, and decyl, or a cycloalkyl group such as cyclopentyl and cyclohexyl, or an aromatic group such as phenyl and tolyl, or an aralkyl group such as benzyl, phenethyl, and phenylpropyl, or an unsaturated alkenyl group such as vinyl, allyl, butenyl, propenyl, isopropenyl, and phenylalkenyl.
[0022] Preferably, R2, R3, R4, R5, and R6 are independently selected from a hydrogen atom and a saturated alkyl group having 1 to 3 carbon atoms; more preferably, R2, R3, R4, R5, and R6 are independently selected from a hydrogen atom, a methyl group, and an ethyl group.
[0023] Furthermore, the component (B) is at least one selected from the group consisting of polyamic acid, polyimide, polyamic acid ester, polyorganosiloxane and poly(meth)acrylate.
[0024] Among them, polyamic acid and polyamic acid ester contain the structural unit represented by the following formula (7), and polyimide contains the structural unit represented by the following formula (8):
[0025]
[0026] In the formula (7) and the formula (8), X represents a tetravalent organic group of a tetracarboxylic acid derivative.
[0027] Z represents a divalent organic group having 2 to 40 carbon atoms.
[0028] R7 and R8 are each independently selected from a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, such as a hydrogen atom, a methyl group, an ethyl group, a propyl group, a butyl group, and the like.
[0029] n is an integer of 2 to 250, for example, 2, 5, 10, 50, 100, 150, 200, or 250.
[0030] (B) Component is preferably at least one of polyamic acid, polyimide, polyamic acid ester, and polyorganosiloxane, and more preferably at least one of polyamic acid and polyimide.
[0031] Furthermore, the organic solvent of the component (C) has a function of dissolving the polymer A and the polymer B. The organic solvent is selected from N-methyl-2-pyrrolidone, γ-butyrolactone, γ-butyrolactam, N,N-dimethylformamide, N,N-dimethylacetamide, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monomethyl ether, butyl lactate, butyl acetate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol ethyl ether, ethylene glycol-n-propyl ether, ethylene glycol-isopropyl ether, ethylene glycol monobutyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, dipropylene glycol monomethyl ether, diisobutyl ketone, isoamyl propionate, isoamyl isobutyrate, diisoamyl ether, ethylene carbonate, propylene carbonate, etc. These solvents can be used alone or in combination of two or more.
[0032] Furthermore, relative to 100 parts by mass of the solid matter of the component (B), the amount of the component (A) is 0.1 to 10 parts by mass, for example, 0.1 parts by mass, 0.3 parts by mass, 0.5 parts by mass, 0.8 parts by mass, 1 parts by mass, 2 parts by mass, 3 parts by mass, 4 parts by mass, 5 parts by mass, 6 parts by mass, 7 parts by mass, 8 parts by mass, 9 parts by mass, and 10 parts by mass.
[0033] Furthermore, relative to 100 parts by mass of the solid matter of component (B), the amount of component (C) is 500-5000 parts by mass, for example, 500 parts by mass, 600 parts by mass, 700 parts by mass, 800 parts by mass, 900 parts by mass, 1000 parts by mass, 1500 parts by mass, 2000 parts by mass, 2500 parts by mass, 3000 parts by mass, 3500 parts by mass, 4000 parts by mass, 4500 parts by mass, and 5000 parts by mass.
[0034] The liquid crystal alignment agent of the present invention can be used to prepare a liquid crystal alignment film of a liquid crystal display element, and in particular can be used to prepare a liquid crystal alignment film with high friction resistance.
[0035] The present invention further provides a liquid crystal display element, which includes a liquid crystal alignment film, and the liquid crystal alignment film is prepared from the liquid crystal alignment agent of the present invention.
[0036] Furthermore, the preparation method of the liquid crystal alignment film can be prepared by a common method in the prior art, which is not difficult for those skilled in the art.
[0037] The present invention provides a liquid crystal alignment agent, which contains nitrogen-containing heterocyclic polysiloxane with a special structure. A liquid crystal display element made of the liquid crystal alignment agent can maintain a high voltage holding rate and has good liquid crystal orientation. Even when physical friction such as friction caused by a spacer occurs, the bright spots can be minimized and the liquid crystal display element has high friction resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The infrared spectra of nitrogen-containing heterocyclic polysiloxanes PS-11, PS-15, PS-14, and PS-18. DETAILED DESCRIPTION
[0039] Hereinafter, each component contained in the liquid crystal aligning agent of this indication and other components mix|blended arbitrarily as needed are demonstrated.
[0040] The liquid crystal aligning agent of this invention contains (A) component, (B) component, and (C) component.
[0041] <Component (A): Polymer A>
[0042] The liquid crystal aligning agent of the present invention contains a polymer A, and the polymer A is at least one selected from the group consisting of nitrogen-containing heterocyclic polysiloxanes represented by the above formula (1).
[0043] Polymer A is prepared by the following steps:
[0044] Step 1, under gas protection, stirring and mixing the organic solvent, nitrogen-containing heterocyclic silane coupling agent monomer and catalyst uniformly;
[0045] Step 2, controlling the temperature of the mixture in step 1 at 0-40°C, adding water dropwise thereto, keeping the mixture warm for reaction after the addition is complete, and then raising the temperature to 50-100°C to continue the reaction;
[0046] Step 3: After the reaction, the organic layer is separated and the volatiles are removed by distillation to obtain a nitrogen-containing heterocyclic polysiloxane.
[0047] Furthermore, in step 1, the nitrogen-containing heterocyclic silane coupling agent monomer is selected from at least one of the structures represented by the following formula (9):
[0048]
[0049] In formula (9), the definitions of R1 and W are consistent with the above definitions.
[0050] In formula (9), R7 is selected from a hydrocarbon group having 1 to 10 carbon atoms, and the hydrocarbon group may be an alkyl group such as methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, etc., or a cycloalkyl group such as cyclopentyl, cyclohexyl, etc., or an aromatic group such as phenyl, tolyl, etc., or an aralkyl group such as benzyl, phenethyl, phenylpropyl, etc., or an unsaturated alkenyl group such as vinyl, allyl, butenyl, propenyl, isopropenyl, phenylalkenyl, etc. Preferably, R7 is a saturated alkyl group having 1 to 10 carbon atoms, and more preferably, R7 is methyl or ethyl.
[0051] Furthermore, when the W group is When the nitrogen-containing heterocyclic silane coupling agent monomer represented by formula (9) is prepared by referring to the preparation method in patent ZL202111145299.6.
[0052] Furthermore, when the W group is
[0053] When, the preparation method of the nitrogen-containing heterocyclic silane coupling agent monomer shown in formula (9) is:
[0054] Category 1: Amide-based nitrogen-containing heterocyclic silane coupling agent monomers:
[0055] The oxazole diamine or imidazole diamine is mixed with a solvent, and then the silane coupling agent SANAH or 3-(trimethoxysilyl)propyl succinic anhydride is slowly added in an amount twice the molar amount of the diamine. After the addition is completed, the reaction is continued at 23-26° C. for 20-22 hours. After the reaction is completed, the nitrogen-containing heterocyclic silane coupling agent monomer of the amic acid type is obtained by distillation under reduced pressure and purification.
[0056] The second category: imide nitrogen-containing heterocyclic silane coupling agent monomer:
[0057] The oxazole diamine or imidazole diamine is mixed with a solvent, and then the silane coupling agent SANAH or 3-(trimethoxysilyl)propyl succinic anhydride is slowly added in a molar amount twice that of the diamine. After the addition is completed, the reaction is continued at 23-26° C. for 20-22 hours, and then a base and anhydride are added to the reaction system for imidization. After the reaction is completed, the solvent, unreacted raw materials and by-products in the system are removed by reduced pressure distillation to obtain an imide-type nitrogen-containing heterocyclic silane coupling agent monomer.
[0058] Category 3: Amide ester nitrogen-containing heterocyclic silane coupling agent monomers:
[0059] The oxazole diamine or imidazole diamine is mixed with a solvent, and then the silane coupling agent SANAH or 3-(trimethoxysilyl)propyl succinic anhydride is slowly added in a molar amount twice that of the diamine. After the addition is completed, the reaction is continued at 23-26° C. for 20-22 hours, and then an esterification agent (N,N-dimethylformamide dimethyl acetal, N,N-dimethylformamide diethyl acetal, etc.) is added to the system for esterification reaction. After the reaction is completed, it is distilled under reduced pressure to obtain an amide ester nitrogen-containing heterocyclic silane coupling agent monomer.
[0060] Optionally, in step 1, the organic solvent is selected from at least one of hydrocarbons, ketones, esters, ethers, and alcohols. The hydrocarbons include, for example, toluene and xylene; the ketones include, for example, methyl ethyl ketone, methyl isobutyl ketone, methyl n-amyl ketone, diethyl ketone, cyclohexanone, etc.; the esters include, for example, ethyl acetate, n-butyl acetate, isopentyl acetate, propylene glycol monomethyl ether acetate, 3-methoxybutyl acetate, ethyl lactate, etc.; the ethers include, for example, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, tetrahydrofuran, dioxane, etc.; the alcohols include, for example, 1-hexanol, 4-methyl-2-pentanol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol mono-n-butyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, etc. The organic solvent is preferably one that is immiscible with water, and these organic solvents may be used alone or in combination of two or more.
[0061] Optionally, in step 1, the catalyst may be one of an acid, an alkali metal compound, an organic base, and the like. Examples of the acid include hydrochloric acid, p-toluenesulfonic acid, and the like; examples of the alkali metal compound include, for example, sodium hydroxide, potassium hydroxide, sodium methoxide, potassium methoxide, sodium ethoxide, potassium ethoxide, and the like; examples of the organic base include, for example, primary and secondary organic amines such as ethylamine, diethylamine, piperazine, piperidine, pyrrolidine, and pyrrole; tertiary organic amines such as triethylamine, tri-n-propylamine, tri-n-butylamine, pyridine, 4-dimethylaminopyridine, and diazacycloundecene; and quaternary organic amines such as tetramethylammonium hydroxide, and the like. Among these organic bases, triethylamine, tri-n-propylamine, tri-n-butylamine, pyridine, 4-dimethylaminopyridine, and tetramethylammonium hydroxide are preferred.
[0062] Optionally, in step 1, the mass ratio of the nitrogen-containing heterocyclic silane coupling agent monomer to the organic solvent is 1:0.5-20, for example, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, preferably 1:1-10.
[0063] Optionally, in step 1, the mass ratio of the nitrogen-containing heterocyclic silane coupling agent monomer to the catalyst is 1:0.01 to 0.3, for example, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, preferably 1:0.01 to 0.1.
[0064] Optionally, in step 2, the mass ratio of the nitrogen-containing heterocyclic silane coupling agent monomer to water is 1:1-50, for example, 1:1, 1:2, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, preferably 1:2-20.
[0065] Optionally, in step 2, the water is added dropwise for 0.5 to 5 h, for example, 0.5 h, 1 h, 2 h, 3 h, 4 h, or 5 h.
[0066] Optionally, in step 2, water is added dropwise at 0-40°C, and the temperature can be 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C. After the water is added dropwise, the reaction is kept warm for 3-6 hours, such as 3 hours, 4 hours, 5 hours, 6 hours. After the reaction, the temperature is continued to rise to 50-100°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, and the reaction is continued at this temperature for 6-12 hours, such as 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours.
[0067] <Component (B): Polymer B>
[0068] The polymer B is at least one selected from polyamic acid, polyimide, polyamic acid ester, polyorganosiloxane and poly(meth)acrylate, preferably at least one of polyamic acid, polyimide, polyamic acid ester and polyorganosiloxane, more preferably at least one of polyamic acid and polyimide.
[0069] <Polyamic acid>
[0070] The polyamic acid as the polymer B in the present invention has a structural unit represented by the above formula (7), and can be obtained by reacting tetracarboxylic dianhydride with diamine.
[0071] <Tetracarboxylic dianhydride>
[0072] As a tetracarboxylic dianhydride used for synthesizing the polyamic acid in this invention, aliphatic tetracarboxylic dianhydride, alicyclic tetracarboxylic dianhydride, aromatic tetracarboxylic dianhydride, etc. are mentioned.
[0073] Examples of the aliphatic tetracarboxylic dianhydride include 1,2,3,4-butanetetracarboxylic dianhydride and the like;
[0074] Examples of the alicyclic tetracarboxylic dianhydride include 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dichloro-1,2,3,4-cyclobutanetetracarboxylic dianhydride, and 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride. , 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 3,3',4,4'-dicyclohexyltetracarboxylic dianhydride, cis-3,7-dibutylcycloheptyl-1,5-diene-1,2,5,6-tetracarboxylic dianhydride, 2,3,5-tricarboxylic acid cyclopentyl acetic dianhydride, bicyclo[2.2.2]-oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, etc.;
[0075] Examples of the aromatic tetracarboxylic dianhydride include 3,4-dicarboxy-1,2,3,4-tetrahydronaphthalene-1-succinic dianhydride, pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl sulfone tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 3,3',4,4'-diphenylethane tetracarboxylic dianhydride, 3,3',4,4'-dimethyldiphenylsilane tetracarboxylic dianhydride, 3,3',4,4'-tetraphenylsilane tetracarboxylic dianhydride, 1,2,3,4-furan tetracarboxylic dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfide dianhydride, and 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfone. Dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenylpropane dianhydride, 3,3',4,4'-perfluoroisopropylidene diphthalic acid dianhydride, 3,3',4,4'-diphenyltetracarboxylic acid dianhydride, bis(phthalic acid)phenylphosphine oxide dianhydride, p-phenylene-bis(triphenyl diacid) dianhydride, m-phenylene-bis(triphenyl phthalic acid) dianhydride, bis(triphenyl phthalic acid)-4,4'-diphenyl ether dianhydride, bis(triphenyl phthalic acid)-4,4'-diphenylmethane dianhydride, ethylene glycol-bis(anhydrotrimellitate), propylene glycol-bis(anhydrotrimellitate), 1,4-butanediol-bis(anhydrotrimellitate), 1,6-hexanediol-bis(anhydrotrimellitate), 1,8-octanediol-bis(anhydrotrimellitate 、2,2-bis(4-hydroxyphenyl)propane-bis(anhydrotrimellitate), 2,3,4,5-tetrahydrofuran tetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-methyl-5-(tetrahydro-2,5-dioxo-3-furyl)-naphtho[1,2-c]-furan-1,3-dione, 1,3,3a,4,5,9b-hexahydro-5-ethyl-5-(tetrahydro-2,5-dioxo-3-furyl)-naphtho[1,2-c]-furan-1,3-dione, 1,3,3a,4,5,9b-hexahydro-7-methyl-5-(tetrahydro-2,5-dioxo-3-furyl)-naphtho[1,2-c]-furan-1,3-dione, 1,3,3a,4,5,9b -Hexahydro-7-ethyl-5-(tetrahydro-2,5-dioxo-3-furyl)-naphtho[1,2-c]-furan-1,3-dione, 1,3,3a,4,5,9b-hexahydro-8-methyl-5-(tetrahydro-2,5-dioxo-3-furyl)-naphtho[1,2-c]-furan-1,3-dione, 1,3,3a,4,5,9b-hexahydro-8-ethyl-5-(tetrahydro-2,5-dioxo-3-furyl)-naphtho[1,2-c]-furan-1,3-dione, 1,3,3a,4,5,9b-hexahydro-5,8-dimethyl-5-(tetrahydro-2,5-dioxo-3-furyl)-naphtho[1,2-c]-furan-1,3-dione, 5-(2,5-dioxo-tetrahydrofuranyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic acid dianhydride, etc.;
[0076] The tetracarboxylic dianhydride may be used alone or in combination of two or more.
[0077] From the perspective of photo-orientation, the tetracarboxylic dianhydride used to synthesize the polyamic acid preferably contains alicyclic tetracarboxylic dianhydride, and more preferably 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2-dimethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, and 1,3-dimethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride. In addition, when two or more dianhydrides are used as tetracarboxylic dianhydrides for synthesizing polyamic acid, the content of dianhydride is preferably 50 mol% or more, and more preferably 70 mol% or more, relative to the total amount of tetracarboxylic dianhydride.
[0078] <Diamine>
[0079] As a diamine used for synthesizing the polyamic acid in this invention, an aliphatic diamine, an alicyclic diamine, an aromatic diamine, etc. are mentioned.
[0080] Examples of the aliphatic diamine include meta-xylylenediamine, 1,3-propylenediamine, tetramethylenediamine, and pentamethylenediamine;
[0081] Examples of the alicyclic diamine include 1,4-diaminocyclohexane, 4,4'-methylenebis(cyclohexylamine), and 1,3-bis(aminomethyl)cyclohexane.
[0082] Examples of the aromatic diamine include p-phenylenediamine, 4,4′-diaminodiphenylmethane, 4,4′-diaminodiphenyl sulfide, 1,5-diaminonaphthalene, 2,2′-dimethyl-4,4′-diaminobiphenyl, 4,4′-diamino-2,2′-bis(trifluoromethyl)biphenyl, 2,7-diaminofluorene, 4,4′-diaminodiphenyl ether, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4′-(p-phenylenediisopropylidene)dianiline, 4,4′-(m-phenylenediisopropylidene)diphenylamine, and 4,4′-(m-phenylenediisopropylidene)diphenylamine. 4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 2,6-diaminopyridine, 3,4-diazopyridine, 2,4-diaminopyrimidine, 3,6-diaminoacridine, 3,6-diaminocarbazole, N-methyl-3,6-diaminocarbazole, N-ethyl-3,6-diaminocarbazole, N-phenyl-3,6-diaminocarbazole, N,N'-bis(4-aminophenyl)-benzidine, N,N'-bis(4-aminophenyl)-N,N'-dimethylbenzidine, 1,4-bis-(4-aminophenyl)-piperazine, 3,5-diaminobenzoic acid, etc.
[0083] The above diamines can be used alone or in combination of two or more.
[0084] <Synthesis of Polyamic Acid>
[0085] The polyamic acid in the present invention can be prepared by a known synthesis method, such as reacting tetracarboxylic dianhydride and diamine in a certain molar ratio in an organic solvent. This method is easy to carry out.
[0086] The ratio of tetracarboxylic dianhydride to diamine is preferably 0.2 to 2 equivalents of the anhydride group of tetracarboxylic dianhydride relative to 1 equivalent of the amino group of the diamine, and more preferably 0.3 to 1.2 equivalents of the anhydride group of tetracarboxylic dianhydride. The closer the equivalent is to 1, the greater the molecular weight of the obtained polyamic acid will be. In addition, the synthesis reaction of polyamic acid is preferably carried out in an organic solvent. The reaction temperature at this time is preferably -20°C to 150°C, and more preferably 0°C to 100°C. In addition, the reaction time is preferably 0.5 hours to 48 hours, and more preferably 2 hours to 24 hours.
[0087] Here, as the organic solvent used for the reaction, any organic solvent can be used as long as it can dissolve the synthesized polyamic acid. Specifically, for example, non-protonic polar solvents such as N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, tetramethylurea, and hexamethylphosphoric triamide; phenolic solvents such as meta-cresol, xylenol, phenol, and halogenated phenols, etc. Furthermore, these organic solvents can be used alone or in combination of two or more.
[0088] In addition, as an organic solvent for the reaction, a poor solvent for the polyamic acid can also be used within the range that the synthesized polyamic acid will not precipitate. As such a poor solvent, for example, alcohols such as methanol, ethanol, isopropanol, cyclohexanol, ethylene glycol, propylene glycol, and ethylene glycol monomethyl ether; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; esters such as ethyl lactate, butyl lactate, methyl acetate, ethyl acetate, butyl acetate, methyl methoxypropionate, diethyl oxalate, and isoamyl propionate; ethers such as diethyl ether, ethylene glycol methyl ether, ethylene glycol propyl ether, ethylene glycol butyl ether, ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, tetrahydrofuran, and diisoamyl ether; halogenated hydrocarbons such as dichloromethane, 1,2-dichloroethane, 1,4-dichlorobutane, and trichloroethane; hydrocarbons such as hexane, heptane, octane, benzene, toluene, and xylene. In addition, these poor solvents can be used individually by 1 type or in mixture of 2 or more types.
[0089] When a poor solvent for polyamic acid is used as an organic solvent for the reaction, the proportion of the poor solvent for polyamic acid used relative to the total amount of the organic solvent used for synthesis is preferably 50wt% (weight percentage) or less, more preferably 40wt% or less, and even more preferably 30wt% or less.
[0090] <Polyimide>
[0091] In the present invention, the polyimide as the polymer B has a structural unit represented by the above formula (8), and can be obtained, for example, by imidizing a polyamic acid by dehydration ring closure.
[0092] The polyimide may be a fully imidized product formed by dehydrating and ring-closing all the amic acid structures of the polyamic acid as its precursor, or a partially imidized product in which only a part of the amic acid structure is dehydrated and ring-closed, and the amic acid structure and the imide ring structure coexist. The imidization rate of the polyimide in the present invention is preferably 50% or more, more preferably 60% or more. The imidization rate is expressed as a percentage of the ratio of the number of imide ring structures to the total number of amic acid structures and imide ring structures of the polyimide.
[0093] The dehydration ring-closure of polyamic acid can be carried out by (i) heating the polyamic acid or (ii) dissolving the polyamic acid in an organic solvent, adding a dehydrating agent and a dehydration ring-closure catalyst to the solution and heating as necessary.
[0094] In the method (i), the reaction temperature is preferably 50° C. to 200° C., more preferably 60° C. to 170° C. If the reaction temperature is less than 50° C., the dehydration ring-closure reaction cannot be fully carried out, and if the reaction temperature exceeds 200° C., the molecular weight of the obtained polyimide may decrease. The reaction time is preferably 1 hour to 48 hours, more preferably 2 hours to 24 hours.
[0095] On the other hand, in the method (ii), as a dehydrating agent, for example, anhydrides such as acetic anhydride, propionic anhydride, and trifluoroacetic anhydride can be used. The amount of the dehydrating agent used is preferably set to 0.01 mol to 20 mol relative to 1 mol of the amic acid structural unit. As a dehydration ring-closing catalyst, for example, tertiary amines such as pyridine, trimethylpyridine, dimethylpyridine, triethylamine, and N-methylpiperidine can be used. Relative to 1 mol of the dehydrating agent used, the amount of the dehydration ring-closing catalyst used is preferably set to 0.01 mol to 10 mol. As the organic solvent used in the dehydration ring-closing reaction, the solvents exemplified as organic solvents used in the synthesis of polyamic acid can be cited. The reaction temperature of the dehydration ring-closing reaction is preferably 0°C to 180°C, and more preferably 10°C to 150°C. The reaction time is preferably 0.5 hours to 20 hours, and more preferably 1 hour to 8 hours.
[0096] The polyimide obtained by the method (i) can be directly supplied to the preparation of a liquid crystal alignment agent, or it can also be supplied to the preparation of a liquid crystal alignment agent after the obtained polyimide is refined. On the other hand, in the method (ii), a reaction solution containing a polyimide can be obtained. The reaction solution can be directly supplied to the preparation of a liquid crystal alignment agent, or it can be supplied to the preparation of a liquid crystal alignment agent after removing a dehydrating agent and a dehydration ring-closing catalyst from the reaction solution by methods such as solvent replacement, or it can be supplied to the preparation of a liquid crystal alignment agent after isolating the polyimide, or it can be supplied to the preparation of a liquid crystal alignment agent after refining the isolated polyimide. The isolation and refining operation of the polyimide can be carried out according to a known method.
[0097] <Polyamic acid ester>
[0098] The polyamic acid ester as the polymer in the present invention can be synthesized, for example, by reacting the tetracarboxylic dianhydride exemplified as the compound for the synthesis of the polyamic acid with other diamines to obtain polyamic acid, and then reacting the obtained polyamic acid with a compound having the specific structure and an epoxy group. Furthermore, the polyamic acid ester may have only an amic acid ester structure, or may be a partially esterified product in which an amic acid structure and an amic acid ester structure coexist.
[0099] The polyamic acid, polyamic acid ester and polyimide obtained in the above manner preferably have a solution viscosity of 10mPa·s to 800mPa·s when they are made into a solution with a concentration of 10wt%, and more preferably have a solution viscosity of 15mPa·s to 500mPa·s. Furthermore, the solution viscosity (mPa·s) of the polymer is a value measured at 25°C using an E-type rotational viscometer for a polymer solution with a concentration of 10wt% prepared using a good solvent for these polymers (e.g., γ-butyrolactone, N-methyl-2-pyrrolidone, etc.). In addition, the polyamic acid, polyamic acid ester and polyimide preferably have a weight average molecular weight of 1000 to 300,000 in terms of polystyrene measured by gel permeation chromatography (GPC), and more preferably the weight average molecular weight is 5,000 to 100,000.
[0100] <Component (C): Organic Solvent>
[0101] The polymer A and polymer B components in the liquid crystal alignment agent of the present invention need to be dissolved in an organic solvent.
[0102] Examples of the organic solvent used in the preparation of the liquid crystal alignment agent of the present invention include N-methyl-2-pyrrolidone, γ-butyrolactone, γ-butyrolactam, N,N-dimethylformamide, N,N-dimethylacetamide, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monomethyl ether, butyl lactate, butyl acetate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol ethyl ether, ethylene glycol-n-propyl ether, ethylene glycol-isopropyl ether, ethylene glycol monobutyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, dipropylene glycol monomethyl ether, diisobutyl ketone, isoamyl propionate, isoamyl isobutyrate, diisoamyl ether, ethylene carbonate, propylene carbonate, and the like. These solvents can be used alone or in combination of two or more.
[0103] <Liquid Crystal Alignment Agent>
[0104] The liquid crystal aligning agent of the present invention is preferably prepared in the form of a solution in order to be suitable for forming a liquid crystal aligning film. The liquid crystal aligning agent of the present invention can be prepared, for example, by dispersing or dissolving the component (A) and the component (B) of the present invention and other components as required in an organic solvent (C).
[0105] Examples of other components include a crosslinking compound, a functional silane compound, a surfactant, and an organic solvent.
[0106] The liquid crystal alignment agent of the present invention preferably has a solid content in the range of 1wt% to 10wt% from the aspects of viscosity and volatility. That is, the liquid crystal alignment agent of the present invention is applied to the surface of the substrate as described later, and preferably heated to form a coating film as a liquid crystal alignment film. At this time, when the solid content is less than 1wt%, the film thickness of the coating becomes too small and it is difficult to obtain a good liquid crystal alignment film. On the other hand, when the solid content exceeds 10wt%, the film thickness of the coating becomes too large and it is difficult to obtain a good liquid crystal alignment film. In addition, the viscosity of the liquid crystal alignment agent increases and the coating characteristics deteriorate.
[0107] Different solid content ranges are selected according to the different ways of coating the liquid crystal alignment agent on the substrate. For example, when using the spin coating method, it is preferred to adjust the solid content to a range of 2.5wt% to 6wt%, so that the solution viscosity becomes a range of 8mPa·s to 40mPa·s. When using the printing method for coating, it is preferred to adjust the solid content to a range of 3wt% to 9wt%, so that the solution viscosity becomes a range of 12mPa·s to 50mPa·s. When using the inkjet method for coating, it is preferred to set the solid content to a range of 1.5wt% to 3.5wt%, so that the solution viscosity becomes a range of 3mPa·s to 15mPa·s.
[0108] The liquid crystal display element manufactured using the liquid crystal alignment agent of the nitrogen-containing heterocyclic polysiloxane provided by the present invention can maintain a high voltage holding rate and good liquid crystal orientation, and can minimize bright spots even when physical friction such as friction caused by spacers occurs, thereby greatly improving the display quality of the liquid crystal display element.
[0109] The present invention is described in more detail below by means of synthesis examples and embodiments, but the present invention is not limited to these embodiments. Unless otherwise specified, the raw materials in the embodiments of the present application are purchased through commercial channels.
[0110] The abbreviations of the compounds used below are as follows:
[0111] <Tetracarboxylic dianhydride>
[0112] DMCBDA: 1,3-Dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride
[0113] PMDA: pyromellitic dianhydride
[0114] <Diamine>
[0115] p-PDA: p-phenylenediamine
[0116] DBA: 3,5-diaminobenzoic acid
[0117] DA-1: Compound represented by the following formula (DA-1)
[0118] <Solvent>
[0119] MIBK: Methyl isobutyl ketone
[0120] NMP: N-methylpyrrolidone
[0121] BC: Butyl Cellosolve
[0122] <Silane coupling agent SCA>
[0123] SCA-1:
[0124]
[0125] SCA-2:
[0126]
[0127] SCA-3:
[0128]
[0129] SCA-4:
[0130]
[0131] SCA-5:
[0132]
[0133] SCA-6:
[0134]
[0135] SCA-7:
[0136]
[0137] SCA-8:
[0138] SCA-9:
[0139] SCA-10:
[0140]
[0141] SCA-11:
[0142]
[0143] SCA-12:
[0144]
[0145] SCA-13:
[0146]
[0147] SCA-14:
[0148] SCA-15:
[0149]
[0150] SCA-16:
[0151]
[0152] Among them, the nitrogen-containing heterocyclic silane coupling agent monomer SCA-1 is prepared according to the method of Example 1 in Patent ZL202111145299.6, SCA-3 is prepared according to the method of Example 2 in Patent ZL202111145299.6, SCA-4 is prepared according to the method of Example 3 in Patent ZL202111145299.6, and SCA-5 is prepared according to the method of Example 4 in Patent ZL202111145299.6.
[0153] Preparation method of SCA-2: In a 500mL three-necked flask equipped with a stirrer and a thermometer, add 250.00g of solvent N-methylpyrrolidone and 0.1mol of 3,5-diamino-1,2,4-triazole in sequence, start stirring, and after 3,5-diamino-1,2,4-triazole is fully dissolved, slowly add 0.2mol of silane coupling agent 3-(trimethoxysilyl)propyl succinic anhydride, and after the addition is completed, continue to react at 25°C for 20 hours, then add 0.4mol of N,N-dimethylformamide dimethyl acetal to the system, continue to react at 25°C for 4 hours, and after the reaction is completed, distill under reduced pressure to obtain SCA-2.
[0154] Preparation method of SCA-6:
[0155] Into a 500 mL three-necked flask equipped with a stirrer and a thermometer, 250.00 g of solvent N-methylpyrrolidone and 0.1 mol of 2-(4-aminophenyl)-5-aminobenzimidazole were added in sequence, and stirring was started. After 2-(4-aminophenyl)-5-aminobenzimidazole was fully dissolved, 0.2 mol of silane coupling agent 3-(trimethoxysilyl)propyl succinic anhydride was slowly added. After the addition was completed, the reaction was continued at 25° C. for 20 hours. After the reaction was completed, the mixture was purified by vacuum distillation to obtain SCA-6.
[0156] Preparation method of SCA-7:
[0157] To a 500 mL three-necked flask equipped with a stirrer and a thermometer, 250.00 g of solvent N-methylpyrrolidone and 0.1 mol of 2-(4-aminophenyl)-5-aminobenzimidazole were added in sequence, and stirring was started. After 0.1 mol of 2-(4-aminophenyl)-5-aminobenzimidazole was fully dissolved, 0.2 mol of silane coupling agent 3-(trimethoxysilyl)propyl succinic anhydride was slowly added. After the addition was completed, the reaction was continued at 25° C. for 20 hours, and then 0.4 mol of pyridine was added to the reaction system. After stirring evenly, 0.4 mol of acetic anhydride was slowly added, and the reaction was carried out at 25° C. for 20 hours. After the reaction was completed, the solvent, acetic anhydride, and the generated acetic acid and pyridine in the system were removed by reduced pressure distillation to obtain SCA-7.
[0158] Preparation method of SCA-8: The same as SCA-6 except that 0.2 mol of 3-(trimethoxysilyl)propyl succinic anhydride was replaced by 0.2 mol of silane coupling agent SANAH (Shin-Etsu Chemical Co., Ltd.).
[0159] Preparation method of SCA-9: except replacing 0.2 mol of 3-(trimethoxysilyl)propyl succinic anhydride with 0.2 mol of silane coupling agent SANAH, the rest is the same as SCA-7.
[0160] The preparation method of SCA-10 is the same as that of SCA-6 except that 0.1 mol of 2-(4-aminophenyl)-5-aminobenzimidazole is replaced by 0.1 mol of 2-(4-aminophenyl)-5-aminobenzoxazole.
[0161] Preparation method of SCA-11: except that 0.1 mol of 2-(4-aminophenyl)-5-aminobenzimidazole is replaced by 0.1 mol of 2-(4-aminophenyl)-5-aminobenzoxazole, the rest is the same as SCA-7.
[0162] Preparation method of SCA-12: except that 0.1 mol of 2-(4-aminophenyl)-5-aminobenzimidazole is replaced by 0.1 mol of 2-(4-aminophenyl)-5-aminobenzoxazole, the rest is the same as SCA-8.
[0163] Preparation method of SCA-13: except that 0.1 mol of 2-(4-aminophenyl)-5-aminobenzimidazole is replaced by 0.1 mol of 2-(4-aminophenyl)-5-aminobenzoxazole, the rest is the same as SCA-9.
[0164] Preparation method of SCA-14: To a 500mL three-necked flask equipped with a stirrer and a thermometer, add 250.00g of solvent N-methylpyrrolidone and 0.1mol of 2-(4-aminophenyl)-5-aminobenzoxazole in sequence, start stirring, and after 2-(4-aminophenyl)-5-aminobenzoxazole is fully dissolved, slowly add 0.2mol of silane coupling agent SANAH, and after the addition is completed, continue to react at 25°C for 20 hours, then add 0.4mol of N,N-dimethylformamide diethyl acetal to the system, continue to react at 25°C for 4 hours, and after the reaction is completed, distill under reduced pressure to obtain SCA-14.
[0165] Preparation method of SCA-15: To a 500mL three-necked flask equipped with a stirrer and a thermometer, add 250.00g of solvent N-methylpyrrolidone and 0.1mol of 4,4'-diaminodiphenyl ether in sequence, start stirring, and after 4,4'-diaminodiphenyl ether is fully dissolved, slowly add 0.2mol of silane coupling agent 3-(trimethoxysilyl)propyl succinic anhydride, and after the addition is completed, continue to react at 25°C for 20 hours. After the reaction is completed, distill under reduced pressure to obtain SCA-15.
[0166] Preparation method of SCA-16: Add 250.00 g of solvent N-methylpyrrolidone and 0.1 mol of 4,4'-diaminobenzanilide in sequence to a 500 mL three-necked flask equipped with a stirrer and a thermometer, start stirring, and after 4,4'-diaminobenzanilide is fully dissolved, slowly add 0.2 mol of silane coupling agent 3-(trimethoxysilyl)propyl succinic anhydride, and continue to react at 25° C. for 20 hours after the addition is completed. After the reaction is completed, distill under reduced pressure to obtain SCA-16.
[0167] The silane coupling agent was characterized by hydrogen nuclear magnetic resonance spectroscopy. Some hydrogen spectrum information is as follows:
[0168]
[0169]
[0170] The evaluation of the products prepared in the following synthesis examples and embodiments was carried out according to the following methods.
[0171] <Infrared spectrum test>
[0172] The synthesized polysiloxane sample was tested by a KBr pellet method using an infrared spectrometer (Shimadzu, IRAffinity-1S) to detect whether the polysiloxane of the present invention was successfully prepared.
[0173] <Molecular weight test>
[0174] The weight average molecular weight (Mw) of the resin was measured by gel permeation chromatography (standard polystyrene conversion). The chromatograph used in the measurement was LC-20AD from Shimadzu Corporation, Japan, the chromatographic column was KF-804 from Showa Denko, and the detector was RID-20A from Shimadzu Corporation, Japan.
[0175] <Viscosity Test>
[0176] Take 2 mL of liquid crystal alignment agent sample and put it into the sample cell of the rotational viscometer (BROOKFIELD DV2T LV), select a suitable range, control the temperature at 25±0.1°C, and perform viscosity test.
[0177] <Evaluation of Friction Resistance>
[0178] After filtering the obtained liquid crystal alignment agent with a 0.22 μm filter, it was applied to the ITO surface of the glass substrate with ITO on the entire surface by spin coating, and placed on a heating plate at 80°C for 120 seconds to volatilize the solvent. Then it was placed in an IR clean oven at 230°C for 20 minutes to form a polyimide film with a thickness of 100 nm. The polyimide film was rubbed with cotton cloth (rubbing roller diameter 140 mm, rotation speed 1000 rpm, moving speed 20 mm / sec, pressing amount 0.5 mm, rubbing 2 times) to form a liquid crystal alignment film. Use a microscope to observe the attachments on the surface of the liquid crystal alignment film at a magnification of 10 times. The fewer the attachments, the smaller the bright spot. The situation where there are almost no attachments in the field of view is recorded as "excellent", the situation where there are less than 10 attachments in the field of view is recorded as "good", the situation where there are 10 to 30 attachments in the field of view is recorded as "medium", and the situation where there are more than 30 attachments in the field of view is recorded as "poor".
[0179] <Liquid Crystal Display Element Production>
[0180] A glass substrate (35 mm in width, 30 mm in length, 0.7 mm in thickness) with a 10 mm × 10 mm ITO electrode was prepared and cleaned with a cleaning agent and pure water. A liquid crystal alignment agent was spin-coated on each ITO surface and heated on a hot plate at 80°C for 120 seconds to evaporate the solvent. It was then placed in a clean oven at 230°C and fired for 20 minutes to form an ITO substrate with a polyimide film with a thickness of 100 nm.
[0181] The coating surface was irradiated with 500 mJ / cm2 of linearly polarized ultraviolet light with an extinction ratio of 25:1 and a wavelength of 254 nm through a polarizer, and then baked in a hot air circulation oven at 230°C for 30 minutes to obtain a substrate with a liquid crystal orientation film with a film thickness of 100 nm.
[0182] Next, take a group (two pieces) of substrates with liquid crystal alignment films, spread 4μm spacer particles on the liquid crystal alignment film of one substrate, and bake on a heating plate at 160°C for 30 minutes to fix the spacer particles on the surface of the liquid crystal alignment film, and then drip liquid crystal (F013 made by Merck). Apply UV and thermosetting sealant (WR7101 made by Kyoritsu Chemical Co., Ltd.) on the liquid crystal alignment film of the other substrate. Make the liquid crystal alignment film surfaces of the two substrates inward and the orientation treatment directions reversely parallel, and then bond them in a vacuum environment. Then use a 365nm UV irradiator (TY-UVP made by Ushio) to give the sealant 2J / cm 2 The sealant is cured by UV irradiation energy and then baked in a clean oven at 120°C for 40 minutes to form a liquid crystal display element.
[0183] The prepared liquid crystal display element was subjected to the following performance tests.
[0184] <Liquid Crystal Orientation Evaluation>
[0185] For the liquid crystal display element manufactured in the above manner, the presence or absence of abnormal regions in the light and dark changes when applying and releasing a 5 V voltage was observed using a microscope with a magnification of 50 times. The situation where no abnormal region was observed was evaluated as "good" liquid crystal orientation, and the situation where the abnormal region was observed was evaluated as "poor" liquid crystal orientation.
[0186] <Voltage Holding Ratio Evaluation>
[0187] The liquid crystal display element was placed in an oven at 60°C, and a 5V voltage was applied to the liquid crystal display element for 60 microseconds. The voltage holding ratio (VHR) was measured after 333.3 milliseconds after the voltage was removed. An AC voltage of V100, 30Hz was applied to the liquid crystal display element for 500 hours, and the VHR was tested again according to the above method as the voltage holding ratio after 500 hours. VHR change rate = (initial voltage holding ratio - voltage holding ratio after 500 hours) / initial voltage holding ratio. A 6254C device manufactured by TOYO Corporation was used as a measuring device.
[0188] <Synthesis of Polymer A>
[0189] Synthesis example 1
[0190] Under nitrogen protection, 100 g of methyl isobutyl ketone (MIBK), 30 g of nitrogen-containing heterocyclic silane coupling agent monomer SCA-1, and 1.5 g of p-toluenesulfonic acid were added to a 250 ml three-necked flask, and the mixture was stirred and mixed evenly, and the system temperature was maintained at 10° C. (reaction temperature 1) to obtain a mixed solution; 150 g of deionized water was dropped into the mixed solution within 4 hours. After the addition was completed, the mixture was kept at 10° C. for 4 hours, and then the temperature was raised to 70° C. (reaction temperature 2) and the reaction was continued for 10 hours; after the reaction was completed, the organic layer was taken out, and the volatiles were evaporated off using a rotary evaporator to obtain nitrogen-containing heterocyclic polysiloxane PS-1.
[0191] Synthesis example 2-20
[0192] The nitrogen-containing heterocyclic polysiloxanes PS-2 to PS-20 were prepared by referring to the method of Synthesis Example 1. The reaction conditions used were selected according to Table 1 below.
[0193] Table 1
[0194]
[0195]
[0196] Characterization of nitrogen-containing heterocyclic polysiloxanes: The synthesized polysiloxanes were characterized by infrared spectroscopy. From the infrared characterization results, it can be seen that each polysiloxane has a -1 The Si-O-Si stretching vibration peak appears, indicating that the alkoxy group has been successfully converted into a Si-O-Si structure by hydrolysis. Among them, the infrared spectra of PS-11, PS-15, PS-14, and PS-18 are as follows: Figure 1 shown.
[0197] Synthesis Example 21
[0198] Polysiloxane PS-21 was prepared according to the method of Synthesis Example 1, except that 30 g of nitrogen-containing heterocyclic silane coupling agent monomer SCA-1 was replaced with 30 g of silane coupling agent monomer SCA-15.
[0199] Synthesis example 22
[0200] Polysiloxane PS-22 was prepared according to the method of Synthesis Example 1, except that 30 g of nitrogen-containing heterocyclic silane coupling agent monomer SCA-1 was replaced with 30 g of silane coupling agent monomer SCA-16.
[0201] <Synthesis of Polymer B>
[0202] Synthesis example 23
[0203] In a 1000 mL three-necked flask equipped with a stirring device and a nitrogen inlet tube, 10.80 g (0.10 mol) of p-PDA, 24.40 g (0.10 mol) of DA-1 and 560.10 g of NMP were added in sequence, and nitrogen was introduced while stirring to dissolve. While stirring the diamine solution, 43.90 g (0.196 mol) of DMCBDA as a dianhydride was added, and then 20.00 g of NMP was added in such a way that the solid content became 12 wt %, and the reaction was stirred at room temperature for 24 hours to obtain a polyamic acid solution (PAA-1) with a solid content of 12 wt %. The M of the polyamic acid solution was 12 wt %. w =42100,M n =21041.
[0204] Synthesis Example 24-25
[0205] Polyamic acid PAA-2 and PAA-3 were synthesized by referring to the synthesis method of Synthesis Example 23, except that the tetracarboxylic dianhydride, diamine and their amounts, and the amount of NMP added for the first time were shown in Table 2.
[0206] Synthesis Example 26
[0207] Take 50g of polyamic acid PAA-2 prepared in Synthesis Example 24, add NMP to dilute to 6 mass%, add acetic anhydride (45g) and pyridine (23g) as imidization catalysts, and react at 50°C for 3 hours. The reaction solution is put into methanol (6000mL), and the resulting precipitate is filtered out. The precipitate is washed with methanol and dried under reduced pressure at 100°C to obtain polyimide powder (PI-4). The imidization rate of the polyimide is 78%, M w =38250,M n =19112.
[0208] Synthesis Example 27
[0209] Polyimide PI-5 was synthesized by referring to the synthesis method of Synthesis Example 26, except that the polyamic acid used was PAA-3.
[0210] Table 2
[0211]
[0212] <Preparation of Liquid Crystal Alignment Agent>
[0213] Example 1
[0214] In a 1000 mL three-necked flask, take 250.0 g of the polyamic acid solution (PAA-1) obtained in Synthesis Example 23, add 1.50 g of PS-1, 131.50 g of NMP, and 163.00 g of BC, stir mechanically for 30 minutes, filter with a 0.22 μm PTFE filter membrane to remove impurities, and obtain a liquid crystal alignment agent (AL-1).
[0215] Examples 2 to 24, 27 and Comparative Examples 1 to 5
[0216] The liquid crystal alignment agent was prepared by referring to the method of Example 1, except that the types and amounts of the polyamic acid solution and polymer A in each example and comparative example were selected according to Table 3 below.
[0217] Embodiment 25
[0218] In a 1000 mL three-necked flask, polyimide powder (PI-4) (30.0 g) and NMP (220.0 g) were added and mechanically stirred at 50°C for 5 hours to dissolve. PS-15 (1.5 g), NMP (131.5 g) and BC (163 g) were added to the solution and mechanically stirred at room temperature for 30 minutes. Impurities were removed by filtering with a 0.22 μm PTFE filter to obtain a liquid crystal alignment agent (AL-25).
[0219] Example 26 and Comparative Example 6
[0220] The liquid crystal alignment agent was prepared by referring to the method of Example 25, except that the types and amounts of the polyimide powder and polymer A in each example and comparative example were selected according to Table 3 below.
[0221] Table 3
[0222]
[0223]
[0224] The liquid crystal alignment agents of the embodiments and comparative examples in Table 3 were evaluated for friction resistance according to the aforementioned method, and then the liquid crystal alignment agents of the embodiments and comparative examples in Table 3 were made into liquid crystal display elements according to the aforementioned method, and the liquid crystal orientation and voltage holding rate of each liquid crystal display element were evaluated according to the aforementioned method. The evaluation results are shown in the following Table 4.
[0225] Table 4. Evaluation results of examples and comparative examples
[0226]
[0227]
[0228]
[0229] As shown in Table 4, compared with the liquid crystal alignment agents AL-30 (Comparative Example 3) and AL33 (Comparative Example 6) that do not use nitrogen-containing heterocyclic polysiloxanes, the friction resistance of the alignment films formed by the liquid crystal alignment agents AL-1 to AL-20, AL-22 to AL-27 that use nitrogen-containing heterocyclic polysiloxanes is evaluated as "excellent", and there is less debris caused by friction. It can be seen that the use of nitrogen-containing heterocyclic polysiloxanes can significantly improve the mechanical strength of the alignment film, and the liquid crystal orientation is good, which can effectively inhibit the reduction of VHR caused by driving.
[0230] By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the polysiloxane of the present invention has an improved effect on friction resistance and voltage holding rate due to the introduction of nitrogen-containing heterocycles.
[0231] By comparing Example 15 with Comparative Examples 4 and 5, it can be seen that the amount of nitrogen-containing heterocyclic polysiloxane needs to be within the specified range to play a good role. In Comparative Example 4, the friction resistance of the formed alignment film was evaluated as "medium", and the liquid crystal orientation was evaluated as "poor". This is because the amount of nitrogen-containing heterocyclic polysiloxane used was too much, resulting in the alignment film being brittle, and the nitrogen-containing heterocyclic polysiloxane accumulated in large quantities on the surface of the alignment film, causing the molecules on the surface of the alignment film that align the liquid crystal to be disordered. In Comparative Example 5, since the amount of nitrogen-containing heterocyclic polysiloxane used was too little, it did not play a role in improving the strength of the alignment film.
[0232] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A liquid crystal alignment agent, characterized in that: Contains polymer A, polymer B and an organic solvent; wherein polymer A is selected from at least one of the nitrogen-containing heterocyclic polysiloxanes represented by the following formula (1): In formula (1), Y is selected from at least one of the structures shown in formula (2) to formula (5), and * represents an insertion site: Wherein, R1 is selected from a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an alkoxy group having 1 to 20 carbon atoms; Wherein, W is at least one of the structures ①, ②, and ③ in the following formula (6), and * represents an accession site: In formula (6), R2 represents a hydrogen atom, and R3, R4, R5, and R6 each independently represent a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms; The polymer B is at least one selected from polyamic acid, polyimide, polyamic acid ester, polyorganosiloxane and poly(meth)acrylate.
2. The liquid crystal alignment agent according to claim 1, characterized in that: R1 is selected from hydrogen atom, methyl group, ethyl group, butyl group and hydroxyethyl group of methacrylate.
3. The liquid crystal alignment agent according to claim 1, characterized in that: R3, R4, R5 and R6 are independently selected from a hydrogen atom, a methyl group and an ethyl group.
4. The liquid crystal alignment agent according to claim 1, characterized in that: The polymer B is at least one of polyamic acid, polyimide, polyamic acid ester, and polyorganosiloxane; wherein the polyamic acid and polyamic acid ester contain a structural unit represented by the following formula (7), and the polyimide contains a structural unit represented by the following formula (8): In formula (7) and formula (8), X represents a tetravalent organic group of a tetracarboxylic acid derivative; Z represents a divalent organic group having 2 to 40 carbon atoms; R7 and R8 are independently selected from a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; n is an integer from 2 to 250.
5. The liquid crystal alignment agent according to claim 1, characterized in that: The polymer B is at least one of polyamic acid and polyimide.
6. The liquid crystal alignment agent according to claim 1, characterized in that: The organic solvent is selected from at least one of N-methyl-2-pyrrolidone, γ-butyrolactone, γ-butyrolactam, N,N-dimethylformamide, N,N-dimethylacetamide, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monomethyl ether, butyl lactate, butyl acetate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol ethyl ether, ethylene glycol-n-propyl ether, ethylene glycol-isopropyl ether, ethylene glycol monobutyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, dipropylene glycol monomethyl ether, diisobutyl ketone, isoamyl propionate, isoamyl isobutyrate, diisoamyl ether, ethylene carbonate, and propylene carbonate.
7. The liquid crystal alignment agent according to claim 1, characterized in that: The amount of polymer A used is 0.1 to 10 parts by mass, and the amount of the organic solvent used is 500 to 5000 parts by mass, based on 100 parts by mass of the polymer B solid matter.
8. Use of the liquid crystal alignment agent according to any one of claims 1 to 7 in preparing a liquid crystal alignment film with high friction resistance.
9. A liquid crystal display element, characterized in that: The invention comprises a liquid crystal alignment film, wherein the liquid crystal alignment film is prepared by the liquid crystal alignment agent according to any one of claims 1 to 7.
Citation Information
Patent Citations
Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element
CN104115057A
Liquid crystal aligning agent, liquid crystal alignment film and liquid crystal display element
CN111095091A
A triazole silane coupling agent, its preparation method, and its application.
CN114456205B
Siloxane resin composition and protective film for touch panel using same
CN102227455A
Liquid crystal aligning agent, manufacturing method for liquid crystal display device, liquid crystal alignment film, liquid crystal display device, polymer and carboxylic acid
CN103525435A